Loss of Fbxw7 expression is a predictor of recurrence in colorectal liver metastasis. (12th October 2017) - Kawashita, Yoichiro; Morine, Yuji; Ikemoto, Tetsuya; Saito, Yu; Iwahashi, Syuichi; Yamada, Shinichiro; Higashijima, Jun; Imura, Satoru; Ogawa, Hirohisa; Yagi, Toshiyuki; Shimada, Mitsuo
Abstract: Background: Fbxw7 is a tumor suppressor through ubiquitination and degradation of multiple oncoproteins. Loss of Fbxw7 is frequently observed in various human cancers. In this study, we examined the role of Fbxw7 expression in colorectal liver metastasis (CRLM) and its mechanism. Methods: Fifty‐six patients with CRLM who undergo curative resection were enrolled. Fbxw7 in tumor tissue was determined by immunohistochemistry. Patients were divided into two groups, the Fbxw7 high and low groups. Clinicopathological factors including miR‐223 expression were compared between the high ( n = 32) and low Fbxw7 groups ( n = 24). Results: Fbxw7 expression in tumor tissues was significantly lower than that in normal tissues. The disease‐free survival in the low Fbxw7 group was significantly worse than that in the high Fbxw7 group, and 3 years disease‐free survival of the low and high Fbxw7 groups were 12.5% and 47.0%, respectively ( P = 0.023). On multivariate analysis, loss of Fbxw7 was detected as one of the independent risk factors for recurrence of CRLM (hazard ratio: 2.390, P = 0.017). Likewise, Fbxw7 expression inversely correlated to miR‐223 expression ( P = 0.017). Conclusion: Loss of Fbxw7 in tumor tissues could be a reliable predictor of recurrence after hepatectomy in patients with CRLM, and miR‐223 might be a possible regulator of Fbxw7. Abstract : Highlight Kawashita and colleagues investigated Fbxw7, a tumor suppressor which acts through ubiquitination and degradation of multiple oncoproteins, in 56 patients after curative hepatectomy for colorectal liver metastasis. Loss of Fbxw7 in tumor tissues could be a reliable predictor of recurrence, and microRNA‐223 might be a possible regulator of Fbxw7.